Overcoming the Clinical–MR Imaging Paradox of Multiple Sclerosis: MR Imaging Data Assessed with a Random Forest Approach - Kac̆ar, K.; Rocca, M.A.; Copetti, M.; Sala, S.; Mesaroš, Š.; Stosić Opinćal, T.; Caputo, D.; Absinta, M.; Drulović, J.; Kostić, V.S.; Comi, G.; Filippi, M. (American Journal of Neuroradiology, 2011)
BACKGROUND AND PURPOSE: In MS, the relation between clinical and MR imaging measures is still suboptimal. We assessed the correlation of disability and specific impairment of the clinical functional system with overall and regional CNS damage in a large cohort of patients with MS with different clinical phenotypes by using a random forest approach. MATERIALS AND METHODS: Brain conventional MR imaging and DTI were performed in 172 patients with MS and 46 controls. Cervical cord MR imaging was performed in a subgroup of subjects. To evaluate whether MR imaging measures were able to correctly classify impairment in specific clinical domains, we performed a random forest analysis. RESULTS: Between-group differences were found for most of the MR imaging variables, which correlated significantly with clinical measures (r ranging from −0.57 to 0.55). The random forest analysis showed a high performance in identifying impaired versus unimpaired patients, with a global error between 7% (pyramidal functional system) and 31% (Ambulation Index) in the different outcomes considered. When considering the performance in the unimpaired and impaired groups, the random forest analysis showed a high performance in identifying patients with impaired sensory, cerebellar, and brain stem functions (error below 10%), while it performed poorly in defining impairment of visual and mental systems (error of 91% and 70%, respectively). In analyses with a good level of classification, for most functional systems, damage of the WM fiber bundles subserving their function, measured by using DTI tractography, had the highest classification power. CONCLUSIONS: Random forest analysis, especially if applied to DTI tractography data, is a valuable approach, which might contribute to overcoming the MS clinical−MR imaging paradox. BMSbenign MSCCcorpus callosumCSTcorticospinal tractEDSSExpanded Disability Status ScaleFAfractional anisotropyGMgray matterMCPmiddle cerebellar peduncleMDmean diffusivityMPRAGEmagnetization-prepared rapid acquisition of gradient echoNAWMnormal-appearing white matterNBVnormalized brain volumePPMSprimary-progressive MSRRMSrelapsing-remitting MSSCPsuperior cerebellar peduncleSPMSsecondary-progressive MS